A comparative study on asset management capability maturity models. (2015) - Mahmood, Muhammad Nateque; Dhakal, Subas; Wiewiora, Anna; Brown, Kerry; Keast, Robyn
Asset service organisations often recognise asset management as a core competence to deliver benefits to their business; however, it is less clear about how organisations know whether their asset management processes are adequate. This paper contends that asset management maturity models, which combine best practices with identified competencies, may provide a useful approach to test the capacity of organisations to manage assets. Existing capability maturity models are subject to wide variations in their implementation and sophistication. Drawing on five dimensions of effective asset management - spatial, temporal, organisational, statistical and evaluation - as identified by Amadi-Echendu et al. (2010), this paper undertakes a comprehensive comparative analysis of six existing maturity models to identify the gaps in key process areas. Results suggest incorporating these dimensions into an integrated approach to assess the maturity of asset-intensive organisations would provide a comprehensive approach towards assessing capabilities of asset service organisations.